Impactos das mudanças tecnológicas e organizacionais na força de trabalho de três empresas do setor agroindustrial de Minas Gerais - Fonseca, Maria Leila Rezende do Vale (2000)
With the opening of the brazilian cconomy, the process of globalization in ali productive, economic and social sectors intensifíed. The work-force in the organizations was one of the sectors that was most affected by the technological and organizational changes oceurredduring this process. Due to the quickness in which the enterprises have to adapt to the new global reality, incorporating innovations in the administrative área, in the methods offinancial capital control and mechanisms to reduce costs, in the produetion technologies, as well as in the use of highly qualifíed work labor,this workproposes an analyis of the impact of thesechanges in the make-up of the work-force and in the demand for training towards the qualification ofworkers with technical educalion at the highschool leveiof the three agricultural-industrial enterprises of Minas Gerais. Two of them are in the food sector (derivatives of cofTee and dairy produets) and one produces chemical substances (fertilizers). The mcthodology used was bascdon the qualitativo rescarch by nieans of studying the historic-organizational case, developing a comparative analyzis of the results obtained and observed in the period of 1990 until 1998. The results and discussion involve a general characterization of the researched enterprises, including the process ofadministrative andindustrial modemization, the strategic and technological aspects of produetion and recruiting or work labor. In general it was observed that the enterprises diversified their product lines, having had considerable strategic invesünents in installations and expansions, marketing, maintanance, and acquisition of more modera machinery and equipment. The enterprises involved in this research have been experiencing intense organizational restrueturing, adopting new methods and administrative and productive practices. With the modemization process, the enterprises are requiring qualifíed work labor and have invested in training. In the hiring process, the workers are required to have minimal schooling at the high school levei or technical schooling of the same levei. According to the perspective ofthe people interviewed, the technical courses offered are not up-to-date. The people interviewed suggest, however, that subjects that deal with human relations be introduced in the curriculum, and that these subjects should be able to relate the theory with the practice by means of technical visits and internships.